Photocatalyst Nanostructured Tioâ‚‚ Powder by Using Hydrothermal Method: a Review - Shamsudin, S.; K. Ahmad, M.; Nafarizal, N.; F. Soon, C.; A. Rahim, R.; H. Mamat, M.; B. Suriani, A.; Shimomura, M.; Murakami, K. (International Journal of Engineering and Technology, 2019)
Over the past decades, Titanium dioxide (TiOâ‚‚) have been studied extensively that give positive impact to its synthesis and fabrication method that resulting discovery of a simple low-temperature hydrothermal method that makes the nanostructure of TiOâ‚‚ easily modified according to the desired application. This paper presents a review of photocatalyst nanostructured TiOâ‚‚ by using hydrothermal method as its fabrication method. The TiOâ‚‚ powder widely used as a photocatalytic application that mainly for self-cleaning and wastewater treatment. Â Rutile phase is stable in the high-temperature region compared to anatase and brookite that metastable in high temperature and photo-catalytic activity, PCA could be enhanced by increasing the number of oxygen. By manipulating the preparation method and thermal treatment, a superior photocatalyst with high surface area and crystallinity which correlated to photocatalytic performance was able to produce. In addition to this, photocatalytic activity of TiOâ‚‚ is substantially dependent on the crystal size, specific surface area, crystal defects, charge separation capacity and the interface between the photocatalyst and the molecules.Â